THE LABUH LARUNG SEMBONYO TRADITION IN TASIKMADU VILLAGE, WATULIMO DISTRICT, TRENGGALEK REGENCY - Agustin, Nela Amanda (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2022)
The Larung Sembonyo tradition is a tradition carried out by the coastal community of Prigi. This tradition is a legacy that must be preserved and preserved as well as an aspect that can be expressed through unwritten habits, taboos and sanctions. One of the traditions of the community is the implementation of the Larung Sembonyo tradition at Prigi Beach, Tasikmadu Village, Watulimo District, Trenggalek Regency, which contains very high local wisdom values. This research was carried out with the aim of describing three things, namely 1) to find out the history of the Larung Sembonyo tradition 2) To find out the process of implementing the Larung Sembonyo tradition 3) To find out the community's efforts in developing the values ​​of local wisdom contained in the Larung Sembonyo tradition. The results obtained from this research are 1) knowing the history of the Larung Sembonyo tradition is done by throwing offerings to the open sea as an expression of gratitude to Allah SWT and to pray for the ancestors who have opened the Prigi Bay area. 2) knowing the process of implementing Larung Sembonyo. 3) Efforts have been made by the people of Tasikmadu Village to preserve the values ​​of local wisdom contained in the Larung Sembonyo tradition, namely applying these values ​​in daily life educating the younger generation to introduce this culture to people outside the region through social media, or in the community.